TRAPP: a tool for analysis of Transient binding Pockets in Proteins - Kokh, Daria B.; Richter, Stefan; Henrich, Stefan; Czodrowski, Paul; Rippmann, Friedrich; Wade, Rebecca C. (Journal of chemical information and modeling, 2013)
We present TRAPP (TRAnsient Pockets in Proteins), a new automated software platform for tracking, analysis, and visualization of binding pocket variations along a protein motion trajectory or within an ensemble of protein structures that may encompass conformational changes ranging from local side chain fluctuations to global backbone motions. TRAPP performs accurate grid-based calculations of the shape and physicochemical characteristics of a binding pocket for each structure and detects the conserved and transient regions of the pocket in an ensemble of protein conformations. It also provides tools for tracing the opening of a particular subpocket and residues that contribute to the binding site. TRAPP thus enables an assessment of the druggability of a disease-related target protein taking its flexibility into account.
Gesehen am 25.03.2021